A photographic atlas of selected regions of the Milky Way - Barnard, Edward Emerson, 1857-1923 (Cambridge University Press, 2011)
"Edward Emerson Barnard's Photographic Atlas of Selected Regions of the Milky Way was originally published in two volumes in 1927. Together these volumes contained a wealth of information, including photographic plates of the most interesting portions of the Milky Way, descriptive text, charts, and data. Only 700 copies were printed, making the original edition a collector's item. Reproduced in print for the first time, this edition combines both volumes of Barnard's Atlas. It directly replicates Barnard's text, and contains high resolution images of the original photographic plates and charts, reordered so that they can be seen together. It also includes a biography of Barnard and his work, a Foreword and Addendum by Gerald Orin Dobek describing the importance of the Atlas and additions to this volume, and a pull-out section with a mosaic of all 50 plates combined in a single panorama"--